Contributions of contrast-enhanced ultrasound (CEUS) to a fetal–placental circulation study (EVUPACUS): a protocol for a prospective comparative study in a population of women undergoing termination of pregnancy - Marine Beaumont; Olivier Morel; Charline Bertholdt; Gabriela Hossu; Aboubaker Cherifi; Anne-Laure Fijean; Juliette Lefebvre; Matthieu Dap (BMJ Open)
Introduction Pre-eclampsia and fetal growth restriction (FGR) are two principal complications of pregnancy related to placental dysfunction. Nevertheless, knowledge of the underlying pathophysiological mechanisms remains inadequate, and only a few tools are available for in vivo assessment of placental perfusion. Contrast-enhanced ultrasound (CEUS) allows organ vascularisation evaluation via a strictly intravascular gas microbubble. The primary aim of this study is to compare placental vascularisation parameters obtained via CEUS between pregnancies with FGR and those without FGR.Methods and analysis This is a single-centre, prospective, comparative, non-randomised, feasible, open and interventional study. We will include 30 women with medical termination of pregnancy divided into two groups: one with severe FGR and the other without FGR. Severe FGR is defined as an estimated fetal weight below the third percentile for gestational age. Women will be informed and recruited in the fetal medicine unit over a period of 48 months. The primary goal of this study is to compare the placental contrast ultrasound parameter measurements according to group. The primary objective is to compare placental contrast ultrasound data in women who undergo medical termination of pregnancy at a gestational age of 16 weeks (38+6 days) between two groups: a group with FGR and a group without FGR. The secondary objectives are as follows: (1) to describe the placental vascularisation parameters measured by CEUS; (2) to describe the parameters for quantifying vascularisation at different gestational ages via CEUS; (3) to study the associations between CEUS data and placental histological data and (4) to establish a biological collection of placentas to increase our knowledge of the development and functions of the placenta during pregnancy. The statistical analysis will include descriptive analysis for all study patients, with quantitative data described by means±SDs, medians, IQRs, and extreme values and qualitative data reported as counts and percentages. Comparisons of placental contrast ultrasound parameters between the two groups will be performed via Student’s t-test or the Mann-Whitney U test on the basis of data normality. Associations between CEUS parameters and placental histology data will be analysed with Spearman or Pearson correlations. Qualitative associations will be studied via analysis of variance or the Kruskal-Wallis test. Box plot representations will be used when applicable. Analyses will be performed with R software, with significance set at p<0.05.Ethics and dissemination This study was approved by the French Ethics Committee, the CPP (Comité de Protection des Personnes) SUD EST II – LYON – FRANCE, on 26 April 2024, with reference number 2023-506936-34-00, and the competent authority ANSM (Agence Nationale de Sécurité du Médicament et des Produits de Santé) authorised the study on 17 May 2024. The results of this study will be published in a peer-reviewed journal and will be presented at relevant conferences.Trial registration numbers NCT06497959; EU CT number: 2023-506936-34-00.